2018
DOI: 10.51325/ijbeg.v1i1.7
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Relationship between Rewards and Employees’ Motivation in Some Selected Non-Profit Organizations in Abuja, Nigeria

Abstract: This study examines the relationship between rewards and employee’s motivation in four selected non-profit organizations in Abuja, Nigeria. The employees of the four organizations (Action Aid Nigeria, African Development Foundation (ADF), African Youth Growth Foundation (AYGF) and Think Nigeria First Initiative) were taken as sample of the study. The objectives of this study were to find out the relationship between rewards and employees’ performance in the non-profit organizations in Abuja, Nigeria and also t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Offering appropriate financial packages to employees also enhances their trust, due to which they develop a sustainable association with an organization. A large pool of talented employees gives a competitive edge to a firm resulting in sustainable growth (Lombardi et al, 2020;Ekhayemhe & Oguzie, 2018). Shibly & Chatterjee (2020) argue that a firm should not ignore the non-financial rewards while focusing on financial rewards.…”
Section: Discussion and Conclusion Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Offering appropriate financial packages to employees also enhances their trust, due to which they develop a sustainable association with an organization. A large pool of talented employees gives a competitive edge to a firm resulting in sustainable growth (Lombardi et al, 2020;Ekhayemhe & Oguzie, 2018). Shibly & Chatterjee (2020) argue that a firm should not ignore the non-financial rewards while focusing on financial rewards.…”
Section: Discussion and Conclusion Discussionmentioning
confidence: 99%
“…Extrinsic rewards do not influence employees in the higher-income group the same way as employees belonging to lower-income groups. Ekhayemhe & Oguzie (2018) based on empirical results, have concluded that financial rewards stimulate employee motivation. That is, an increase in rewards would increase employee performance and motivation.…”
Section: Financial Rewards and Employee Motivationmentioning
confidence: 99%
“…These factors are intrinsic and extrinsic (motivators, and hygiene). Intrinsic factors encourage employees to work harder, and extrinsic factors do not inspire employees to work harder but will cause them to become apathetic if they are not present (Ekhayemhe & Oguzie, 2018). Extrinsic factors do not create motivation.…”
Section: Introductionmentioning
confidence: 99%